Film as Philosophy (Raparin Journal of Humanities (RJH), 2022)
Although the relationship between film and philosophy begins in the early twentieth century with Hugo Munsterberg’s book ''The Photoplay: A Psychological Study'', only in the late twentieth century and early twenty-first century the relationship take into account seriously among both philosophers and film theorists. As a result, an intense philosophical debate has arisen about what is film-philosophy? What is the relationship between film and philosophy? Are films genuinely capable of doing philosophy? Or does film capable of being a philosophical work (text)? Although almost all participants in this debate acknowledge that films can, at minimum, bring a philosophical issue to the awareness of their audiences, there is disagreement about how much more films can do philosophically.  In this paper, I will analyse, on the one hand, the historical relationship between film and philosophy, on the other hand, analyse the film as philosophy thesis.This paper has been divided into two parts and each part is also subdivided into two sections. In the first part, I will explore the historical relationship between film and philosophy: doubting film as art (section one) and photography and technological reproduction (section two), then in the second part, I will analyse the film as philosophy thesis: explore the philosophy in film (section one) and examine the film as philosophy (section two). In this paper, I will apply the critical analysis method to examine the film as philosophy thesis.